2019
DOI: 10.1080/21688370.2019.1608759
|View full text |Cite
|
Sign up to set email alerts
|

Occludin knockdown is not sufficient to induce transepithelial macromolecule passage

Abstract: Reiche (2019) Occludin knockdown is not sufficient to induce transepithelial macromolecule passage, Tissue Barriers, 7:2, 1612661, ABSTRACT Occludin, a tight junction protein, has been reported to regulate barrier functionparticularly the leak pathway for larger solutesin epithelia. Therefore, we aimed to precisely define its role in macromolecule passage at single cell-cell junctions. A combination of varying occludin expression by transient and stable knockdown including systematic seeding strategies was em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 44 publications
1
14
0
1
Order By: Relevance
“…Several groups have reported no effect of occludin knockdown on Leak Pathway permeability in MDCK II cells [ 79 , 130 , 131 , 132 ]. Occludin knockdown in Caco-2 cells was reported to increase Leak Pathway permeability [ 100 , 133 ], although this was later disputed [ 134 ]. Occludin overexpression did not alter Leak Pathway permeability in MDCK II cells [ 104 , 130 ].…”
Section: What Cell Components Are Part Of the Leak Pathway?mentioning
confidence: 99%
“…Several groups have reported no effect of occludin knockdown on Leak Pathway permeability in MDCK II cells [ 79 , 130 , 131 , 132 ]. Occludin knockdown in Caco-2 cells was reported to increase Leak Pathway permeability [ 100 , 133 ], although this was later disputed [ 134 ]. Occludin overexpression did not alter Leak Pathway permeability in MDCK II cells [ 104 , 130 ].…”
Section: What Cell Components Are Part Of the Leak Pathway?mentioning
confidence: 99%
“…Van Itallie et al [88] reported that overexpression of occludin enhanced and occludin knockdown diminished the ability of cytokines to alter TER and permeability of large solutes in MDCK Type II renal epithelial cells. Lack of an effect of occludin content on the permeability of fluorescein-dextrans across Caco-2 intestinal epithelial cell monolayers was reported by Richter et al [105]. In contrast to the above findings, the paracellular permeability of 3 kDa fluorescein-dextran [106] and mannitol [107] in MDCK Type II renal epithelial cells was reported to be increased by over-expression of occludin protein.…”
Section: What Are the Molecular Components Of The Leak Pathway?mentioning
confidence: 85%
“…Our speculative model of Leak Pathway permeability suggests that any stimulus which decreases the extent of interconnection among the tight junction proteins or, possibly, the interaction of tight junction proteins with the cytoskeleton could cause a "relaxing" of the macromolecular lattice leading to increased breaks in the claudin network and increased porosity (Figure 1b). If this occurs at a small number of sites within a cell population, as suggested by the studies of Richter et al [105,124] and Stephenson et al [125], this would lead to increased Leak Pathway permeability without altering Pore Pathway permeability. If these interactions are disrupted on a more global scale, however, this would lead to increases in the tight junction permeability to both macromolecules and small ions and solutes as these solutes cross the epithelium through these large disruptions of the tight junction structure.…”
Section: What Is the Leak Pathway?mentioning
confidence: 97%
See 1 more Smart Citation
“…However, Saitou et al [27] and Schulzke et al [28] have shown that occludin knockout mice present normal TJ strand formation and normal barrier function. Furthermore, the hypothesis that occludin expression might define the epithelial leak pathway for macromolecules was not confirmed [29].…”
Section: The Intestinal Barriermentioning
confidence: 99%